Epigean arthropod succession along a 154-year glacier foreland chronosequence in the Forni Valley (Central Italian Alps) - M. Gobbi; F. De Bernardi; M. Pelfini; B. Rossaro; P. Brandmayr (Institute of Arctic and Alpine Research, University of Colorado, 2006)
The 154-year (1850–2004) chronosequence of the Forni Glacier foreland has been studied by sampling ant, centipede, ground beetle, and spider species assemblages. Species numbers increase with terrain age along the chronosequence from 2 to 26 on the oldest soils. Thirty-nine species were collected; species richness and diversity (Shannon’s Index) of communities are correlated to the year of soil deglaciation. Shannon Index values increase with sites deglaciated between 1 and 61 years ago; sites deglaciated between 61 and 78 years ago produce similar values, and those deglaciated 78 to 154 years ago show a further increase in diversity. Ground beetles and spiders are found at all sites, while ants and centipedes were associated with mature forest soils. On the glacier surface, pioneer species such as the wolf-spider Pardosa saturatior and the ground beetle Oreonebria castanea permanently inhabit the supraglacial detritus surviving on trophic resources. Wingless ground beetle species are associated with mature soils, especially those with high hydric stability. Open land species typical of primary succession are found in the pioneer and intermediate stages, while community assemblages found on older terrain are linked to forest vegetation structure and dynamics.